2014
DOI: 10.3389/fonc.2014.00167
|View full text |Cite
|
Sign up to set email alerts
|

Activated Ras Signaling Pathways and Reovirus Oncolysis: An Update on the Mechanism of Preferential Reovirus Replication in Cancer Cells

Abstract: The development of wild-type, unmodified Type 3 Dearing strain reovirus as an anticancer agent has currently expanded to 32 clinical trials (both completed and ongoing) involving reovirus in the treatment of cancer. It has been more than 30 years since the potential of reovirus as an anticancer agent was first identified in studies that demonstrated the preferential replication of reovirus in transformed cell lines but not in normal cells. Later investigations have revealed the involvement of activated Ras sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 71 publications
0
53
0
Order By: Relevance
“…In many tumor cells the activation of this pathway is inhibited by upregulated Ras signaling via epidermal growth factor receptor mutations [48]. While activated Ras signaling appears important to reovirus replication, the mechanism of oncolysis remains unclear and is the source of ongoing research [49].…”
Section: Reovirusmentioning
confidence: 99%
“…In many tumor cells the activation of this pathway is inhibited by upregulated Ras signaling via epidermal growth factor receptor mutations [48]. While activated Ras signaling appears important to reovirus replication, the mechanism of oncolysis remains unclear and is the source of ongoing research [49].…”
Section: Reovirusmentioning
confidence: 99%
“…Our findings could correlate with data obtained with other members of the Reoviridae family. Indeed, activation of the EGF signaling pathway has been correlated with increased reovirus replication and spread through the regulation of multiple steps of the infectious life cycle, including viral uncoating and disassembly, viral protein translation, and the generation of viral progeny (67)(68)(69). However, and in contrast to reovirus (70), we showed that the activation of the MAPK/ERK pathway by BTV-NS3 does not contribute to its ability to inhibit the induction of IFN-␣/␤.…”
Section: Btv-ns3 Inhibits the Induction Of Ifn-␣/␤ Independently Of Mmentioning
confidence: 99%
“…Oncolytic viruses consist of both naturally occurring and genetically modified viral vectors with specificity for and propensity to kill tumor cells [718,34]. OVs have emerged as favorable options for glioma therapy because they have tumor and/or neurotropism, and trigger multifaceted responses including oncolysis and oncolysis-mediated stimulation of antitumor immunity, with minimal toxicity.…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…It does not cause any disease in adult humans and therefore is an attractive candidate for oncolytic virotherapy. Reovirus is a natural oncolytic dependent on activated Ras and its downstream effectors for tumor lysis activity, which also spares normal cells [18,34]. Although Ras signaling in cancer cells affects several events of the Reovirus replication cycle, the infectivity of Reovirus is a determining factor of oncolytic potential.…”
Section: Oncolytic Virusesmentioning
confidence: 99%
See 1 more Smart Citation